Chinese currency exchange rates analysis : risk management, forecasting and hedging strategies /: risk management, forecasting and hedging strategies. (2017) - Du, Jiangze, 1988-; Wang, Jying-Nan; Lai, Kin Keung; Wang, Chao
No abstract available